Evaluation of unconfined hydrogen deflagration characteristics under different turbulence and combustion models: The influence of barrier wall position - Lei, Baiwei; Wu, Zeping; Li, Zou; Li, Xiaotang (Physics of fluids (1994), 2025)
Hydrogen poses a significant risk of explosion, particularly in open spaces. To mitigate the risk of hydrogen explosions, barrier walls are commonly used as a protective measure in practical engineering. However, due to the high cost of experimentation and limitations in monitoring methods, computational fluid dynamics (CFD) simulations play a crucial role in combustion dynamics research. To ensure the accuracy and reliability of CFD simulation results, it is essential to select appropriate combustion and turbulence models. This paper evaluated the applicability of seven combustion models, seven correlations of turbulent flame speed models, and three turbulence models in simulating hydrogen deflagration in open spaces based on GASFLOW-Multi-Physics-Integration. The results showed that the modified multi-phenomenon turbulent burning velocity model, the Schmidt correlation model, and the detached eddy simulation turbulence model provided high computational accuracy in predicting hydrogen deflagration behavior. Additionally, it was found that in open spaces, Darrieus-Landau instability inhibited flame propagation, while flame stretch and thermal-diffusive instability significantly accelerated it. The study further analyzed the hydrogen deflagration characteristics at different barrier wall positions, revealing that while placing the barrier walls closer to the ignition source significantly reduced the explosion hazard in the rear area, it simultaneously increased the damage in the front area. Additionally, the effective protective range of the barrier wall was dependent on its distance from the ignition source. As the distance between the barrier wall and the ignition source increased, its ability to attenuate the blast wave gradually decreased, leading to a reduction in the effective protective range.